Numerical analysis of a planing boat in head waves using a 2D+t method. Issue 3 (October 2015) - Haase, H.; Soproni, J. P.; Abdel-Maksoud, M.
Abstract : The flow around a planing boat is strongly influenced by non-linearities. These have to be taken into account for accurate calculations of the hydrodynamic forces acting on the boat hull. The non-linearities include breaking waves and in general strong deformations of the free surface. Furthermore, the underwater geometry of the boat can change significantly when the boat travels in a seaway or when trim or sinkage change. Therefore, the dynamic behaviour of a planing boat is also strongly non-linear. The 2D+t theory based on a boundary element method (BEM) is a suitable approach, which accounts for the mentioned non-linearities and is also very efficient when compared to common finite volume methods. In this paper, a 2D+t method is employed to investigate the motion behaviour of a prismatic planing boat in head waves. The calculated forces and accelerations are validated by experimental data. A correction of three-dimensional effects, which are not captured by the 2D+t method, is applied and the influences of the correction on the results are investigated.